2021
DOI: 10.1001/jamapsychiatry.2021.0762
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mitochondrial Biogenesis With Variable Penetrance of Schizophrenia

Abstract: that underlie variable penetrance for neuropsychiatric illness in the context of genetic variants that carry elevated risk can advance novel treatment approaches for these disorders.OBJECTIVE To test the hypothesis that mitochondrial compensation is associated with the variable penetrance of schizophrenia in the 22q11.2 deletion syndrome (22q11DS). DESIGN, SETTING, AND PARTICIPANTSThis case-control study compared measures of mitochondrial function and the expression of related genes in 14 induced pluripotent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…Consistent with a possible role of PGC-1α in the 22q11DS, recent results obtained from iPSC derived neurons of 22q11patients with or without SCZ have shown that variable penetrance to the development of SCZ is influenced by compensatory mitochondrial biogenesis that occurs in patients with 22q11DS without SCZ (Li et al, 2021). Indeed, in the 22q11DS without SCZ, expression of nuclear genes encoding ETC subunits, and of multiple mitochondrial encoded genes, were upregulated, as was mitochondrial DNA content and the expression of genes affecting mitochondrial biogenesis and function, such as PGC-1α and PPARα, in human induced pluripotent stem cells (hiPSC) from the 22q11DS without SCZ, thus suggesting that the 22q11DS group without SCZ is characterized by effective compensation for the various mitochondrial abnormalities present in the 22q11DS group with SCZ.…”
Section: Mitochondria Dysfunctions In Schizophrenia: Is There a Role ...supporting
confidence: 61%
See 3 more Smart Citations
“…Consistent with a possible role of PGC-1α in the 22q11DS, recent results obtained from iPSC derived neurons of 22q11patients with or without SCZ have shown that variable penetrance to the development of SCZ is influenced by compensatory mitochondrial biogenesis that occurs in patients with 22q11DS without SCZ (Li et al, 2021). Indeed, in the 22q11DS without SCZ, expression of nuclear genes encoding ETC subunits, and of multiple mitochondrial encoded genes, were upregulated, as was mitochondrial DNA content and the expression of genes affecting mitochondrial biogenesis and function, such as PGC-1α and PPARα, in human induced pluripotent stem cells (hiPSC) from the 22q11DS without SCZ, thus suggesting that the 22q11DS group without SCZ is characterized by effective compensation for the various mitochondrial abnormalities present in the 22q11DS group with SCZ.…”
Section: Mitochondria Dysfunctions In Schizophrenia: Is There a Role ...supporting
confidence: 61%
“…Among the most important risk factors for SCZ, abnormalities in energy mitochondrial metabolism have been found in functional assays and in magnetic resonance spectroscopy studies on SCZ patients (Jensen et al, 2006;Maurer et al, 2001;Öngür et al, 2009;Regenold et al, 2009, Adams et al, 2022 and an analysis of several published studies on genomic, transcriptomic, and proteomic factors associated with SCZ revealed 295 genes that mediate mitochondrial structure or function (Hjelm et al, 2015;Lam et al, 2019;Li et al, 2021;Schulmann et al, 2019;Vawter et al, 2021). Moreover, 22 genes encoding mitochondrial proteins have been mapped within the 108 risk loci (encompassing more than 300 genes) identified by the largest SCZ genome-wide association studies (GWAS) to date (Hjelm et al, 2015;Lam et al, 2019;Li et al, 2021;Ripke et al, 2013;Schulmann et al, 2019;Vawter et al, 2021) and further studies show a decrease of factors and enzymes involved in the production of energy (i.e., adenosine triphosphate-ATP-generation and storage) (Iwamoto et al, 2005;Karry et al, 2004;Klushnik et al, 1991;Middleton et al, 2002;Pennington et al, 2008;Washizuka et al, 2009). Alterations in mitochondrial activity have been consistently reported in SCZ patients: for example, reduced energy metabolism has been reported in patients with psychosis (Regenold et al, 2012) and phosphorous magnetic resonance studies (31P-MRS) reported lower levels of ATP and phosphocreatine in brain of patients with SCZ (Volz et al, 2000).…”
Section: Mitochondria Dysfunctions In Schizophrenia: Is There a Role ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The potential beneficial effects of up regulating mitochondrial function have been suggested by the rapamycin inhibition of mTORC1 which decreased viral replication ( 23 ). Viral pathology might also be mitigated by neutralizing miR-2393 ( 34 ) and activation of mitochondrial biogenesis with bezafibrate ( 56 ).…”
Section: Discussionmentioning
confidence: 99%